Voltage and Current harmonics caused by Power Factor Correction: Case Study in TL Lamp Load - Budiyanto, Ma'un (IJENS, 2016)
Lamp tube (TL) lamp with conventional ballast has a low power factor, so it is necessary to increase the power factor by adding a capacitor. Capacitors including non-linear load, so that the addition of the capacitor causing an increase in nonlinear loads. Nonlinear load provides output waveform that is not linear, causing the current waveform and the output voltage is not the same as the input waveform (distorted). The phenomenon of distorted voltages/currents causes the appearance of harmonics. The objective of the research is to show harmonic of currents and voltages before and after the addition of the capacitor. This research conducted was in the laboratory of Electrical Engineering of Vocational School UGM. The research used TL 36W lamps with conventional ballasts and capacitors F 3.2 and 4.5 F. The results show that fluorescent lamp with a conventional ballast has a power factor = 0.514, = 11.1% harmonic current and voltage harmonics 3.7%. The addition of 3.25 F obtained capacitor power factor = 0.876, = 16.3% harmonic current and voltage harmonic = 3.6%. While the addition of 4.5 F obtained capacitor power factor = 0.957, = 21.5% harmonic currents and harmonic voltage = 3.7%